2010
DOI: 10.1039/b922284g
|View full text |Cite
|
Sign up to set email alerts
|

The first isoform-selective protein biosensor: a metallothionein potentiometric electrode

Abstract: The construction of a biosensor membrane by embedding mammalian Zn(7)-MT1 complexes as ionophores in a polysulfone matrix resulted in precise, accurate and, significantly, selective electrodes for MT1 quantification, so that the presence of other mammalian MT isoforms did not interfere in MT1 measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Hence voltammetry, chronopotentiometry and polarography applications have lowered the detection range to as low as 10 -7 to 10 -10 M, and recently even zeptomolar sensitivity has been reported. Despite these attractive perspectives, electrochemical approaches entail high preparation purity, due to the interference caused by different compounds in the sample [146]. Electrochemical methods are used mainly detection of MTs as environmental pollution biomarker.…”
Section: Electrochemical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence voltammetry, chronopotentiometry and polarography applications have lowered the detection range to as low as 10 -7 to 10 -10 M, and recently even zeptomolar sensitivity has been reported. Despite these attractive perspectives, electrochemical approaches entail high preparation purity, due to the interference caused by different compounds in the sample [146]. Electrochemical methods are used mainly detection of MTs as environmental pollution biomarker.…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…In comparison to the bare carbon paste electrode the detection limit of the sensor was ten times lowered making it comparable to modified carbon paste electrodes. A precise, accurate and, significantly, selective electrodes for MT1 quantification, were presented by Capdevila et al [146] The membrane was created by embedding mammalian Zn-7-MT1 complexes as ionophores in a polysulfone matrix. It was proved that the presence of other mammalian MT isoforms do not interfere in MT1 measurement.…”
Section: Metallothionein As a Part Of Metal-detecting Electrochemicalmentioning
confidence: 99%
“…The majority of known electrochemical biosensors are based on immobilized specific biomolecules, such as proteins, enzymes, nuclear acids, antibodies, and antigens on the modified electrodes [1][2][3][4][5][6][7][8]. These resulting biomolecule-based devices usually show high sensitivity and specificity due to the high loading of enzymes on the nanoparticles [9][10][11][12].…”
mentioning
confidence: 99%
“…Recently, Capevila et al demonstrated a biosensor membrane by embedding mammalian Zn 7 -MT1 complexes as ionophores in the analysis of MT1, which opens up a broad range of possibilities in the use of small proteins or metalloproteins as sensing elements for potentiometric sensors [7]. In this paper, we report a novel potentiometric detection strategy that makes use of protamine as sensing element in organic membrane to offer a very promising method for simple and selective sensing of heparin.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases of practical relevance, however, blood electrolytes such as lipophilic anions thiocyanide (SCN À ) and salicylate (Sal À ) strongly interfere with the heparin response [4]. A significant advance in heparin detection involves the use of protamine sensor as endpoint detector titration of heparin with protamine to avoid such interferences, but such titration methodology complicates the analysis procedure [5,6].Recently, Capevila et al demonstrated a biosensor membrane by embedding mammalian Zn 7 -MT1 complexes as ionophores in the analysis of MT1, which opens up a broad range of possibilities in the use of small proteins or metalloproteins as sensing elements for potentiometric sensors [7]. In this paper, we report a novel potentiometric detection strategy that makes use of protamine as sensing element in organic membrane to offer a very promising method for simple and selective sensing of heparin.…”
mentioning
confidence: 99%